(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Monolithic zirconia crowns have become a routine prosthodontic option because of their strength, biocompatibility and compatibility with digital workflows. However, accelerated chairside sintering protocols may alter shrinkage, marginal adaptation, internal fit and fracture resistance. Objective This in vitro study compared the marginal adaptation, internal fit and fracture resistance of CAD/CAM monolithic zirconia crowns fabricated using conventional and high-speed sintering protocols. Methods Forty-five standardized mandibular first molar dies were prepared and digitally scanned. Full-contour crowns were designed with a 50 μm cement spacer and allocated into three groups (n=15 each): conventionally sintered 4Y-TZP zirconia (CS-Zr), high-speed sintered 4Y-TZP zirconia (HS-Zr) and CAD/CAM lithium disilicate crowns (LD) as a ceramic comparator. Marginal and internal gaps were measured using a silicone replica technique and stereomicroscopy. After adhesive cementation, thermocycling and mechanical aging, fracture resistance was tested using a universal testing machine. Results Mean marginal gap was significantly lower in HS-Zr (67.9 ± 8.7 μm) than CS-Zr (82.6 ± 10.9 μm) and LD (76.4 ± 9.8 μm) (p<0.001). Mean internal gap was lowest in HS-Zr (91.8 ± 11.6 μm), followed by CS-Zr (103.5 ± 13.4 μm) and LD (112.7 ± 15.1 μm) (p=0.002). Fracture resistance was significantly higher for CS-Zr (2386.4 ± 286.7 N) and HS-Zr (2264.8 ± 254.3 N) than LD (1542.3 ± 214.6 N) (p<0.001). Conclusion: High-speed sintered zirconia produced clinically acceptable adaptation and fracture resistance, supporting its use in single-visit posterior prosthodontics when validated material-specific protocols are followed. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S305-S310